Story of a Beautiful Country - Matabane, Khalo (Edkins, Don, 2004)
Duration: 01:13:00 What is the current atmosephere in South Africa? What do the local people think of their country, about its past, its future and how do they live there? These and similar questions are asked by director Khalo Matabane, who, while searching for the answers was inspired by a South African proverb which says "a man who wants to get to know his country must set off on a journey." From his native village in the North of the country he sets out by car as far as Cape Town and meticulously records not only the various features of the passing landscape, but also those of its inhabitants. In the vast majority of cases he allows them to sit in the backseat of his car and during the journey attentively listens to their stories. Everyone agrees on the fact that they are proud of their country, but at the same time it is evident in their speech how much evil was committed by racial segregation during the period of apartheid. Hope for the future can be seen in the mixed married couple Henry and Sinta Mokok, whose open opinions are expressed at length during their playful return from a night club. At the end of this pleasantly and leisurely flowing road movie, the creators finally step out of the car. Among the picturesque scenery here stands one of the first tengible reminders of the arrival of the Europeans on the "dark continent." The cross of Vasco de Gama from 1497 symbilically reminds us of the beginning of the colonization of South Africa and all the problems, which are still associated with it to this day.